DESCRIPTION OF THE RELATIONSHIP BETWEEN GENDER AND PATIENTS STATUS OF COVID-19 IN INDONESIA - Nawawi, M. Ichsan; Pathuddin, Hikmawati; Masrifah, Rofia (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2021)
Background: Anecdotal evidence suggests that Coronavirus 2019 (COVID-19), caused by the SARS-CoV-2 coronavirus, shows differences in morbidity and mortality between the gender. The gender category is one of the simple categories but it is very important to look at the relationship between gender (male/female) and Covid-19 positive patient status (life/death). Metods: In this study used odds ratios. Result: The results showed that the chances of men affected by Covid-19 to recover were 0.75 times the chances of women with positive Covid-19 to recover. Recommandation: For further research, can use more diverse variables and larger sample sizes